2014
DOI: 10.2527/jas.2013-6978
|View full text |Cite
|
Sign up to set email alerts
|

A post-transcriptional mechanism regulates calpastatin expression in bovine skeletal muscle1

Abstract: ABSTRACT:The objective of this study was to investigate whether single nucleotide polymorphisms (SNP) in the calpain 1 (CAPN1), calpain 3 (CAPN3) and calpastatin (CAST) genes, which have been shown to be associated with shear force and tenderness differences in the skeletal muscle of cattle, contribute to phenotypic variation in muscle tenderness by modulating the transcriptional activity of their respective gene. The mRNA expression of the calpain and CAST genes was assessed in the longissimus lumborum muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Meanwhile, the rapidity of CAPN3 autodegradation was also thought to through regulate its activity in N-terminal (Ono et al, 2014). Although it has also been demonstrated to be a candidate protein for meat tenderness in mammals, including cattle (Robinson et al, 2012;Nattrass et al, 2014) and pigs (De Smet et al, 2003), its roles, particularly its physiological activities, in geese have not been sufficiently examined. Therefore, this work will have the potential to increase our understanding of the functional roles of CAPN3 gene during improving goose meat quality provides a molecular basis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the rapidity of CAPN3 autodegradation was also thought to through regulate its activity in N-terminal (Ono et al, 2014). Although it has also been demonstrated to be a candidate protein for meat tenderness in mammals, including cattle (Robinson et al, 2012;Nattrass et al, 2014) and pigs (De Smet et al, 2003), its roles, particularly its physiological activities, in geese have not been sufficiently examined. Therefore, this work will have the potential to increase our understanding of the functional roles of CAPN3 gene during improving goose meat quality provides a molecular basis.…”
Section: Discussionmentioning
confidence: 99%
“…The next question to be answered is what causes the differences in myofibrillar proteolysis in skeletal muscle of Bos taurus and Bos indicus. To answer that question a great body of evidence has been amassed to evaluate the mRNA abundance and/or the allelic as well as genotype frequencies of CAPN1 and CAST and their polymorphism to assess the possible mechanisms related to myofibrillar proteolysis in the skeletal muscle (Curi et al 2009(Curi et al , 2010Giusti et al 2013;Nattrass et al 2014). Although most of these studies were developed to investigate beef tenderness, their results may reflect the effects of these genes on proteolysis in a live skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these studies were developed to investigate beef tenderness, their results may reflect the effects of these genes on proteolysis in a live skeletal muscle tissue. Nattrass et al (2014) speculated that the level of gene expression of CAPN1 and CAST would ultimately influence the activity of the proteins encoded by these genes (Calpain and Calpastatin), thus leading to the difference in the extent of skeletal muscle proteolysis. However, a genome scan performed by Tizioto et al (2013) found a small effect of single nucleotide polymorphisms (SNPs) in CAPN1 and CAST in proteolysis and consequently Warner-Bratzler shear force on beef from Nellore cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Niciura et al (48) found that CAST was expressed twice as much in muscle of homozygous GG as in heterozygous AG in the CAST T1 marker. Natrass et al (49) investigated this relationship in Bos indicus and Bos taurus cattle and found differences in CAPN1 and CAST gene expression between favourable and unfavourable allelic variants of these genes (CAPN1 4751 and CAST T1 markers), indicating a polymorphic effect on gene expression. These findings suggest that differences in tenderness explained by gene markers could be a consequence of the alteration in their mRNA levels, protein activity and rate and (or) the extent of postmortem proteolysis in skeletal muscle.…”
Section: El Nuevo Marcador Capn1 4751 Fue úTil En Poblaciones De Bovimentioning
confidence: 99%